2002
DOI: 10.1034/j.1600-0447.106.s415.5.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving remission from depression with venlafaxine and venlafaxine extended release: a literature review of comparative studies with selective serotonin reuptake inhibitors

Abstract: Objective:  To evaluate data supporting the ability of venlafaxine, an antidepressant with a dual mechanism of action, to produce remission from depression. Method:  Review of multicentre, double‐blind, randomized studies comparing venlafaxine or venlafaxine extended release (XR) with a selective serotonin reuptake inhibitor (SSRI), using Hamilton Depression Rating Scale total scores in the range of ≤7 and <10 as the final outcome measure, to evaluate the ability of venlafaxine/venlafaxine XR to produce full r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…We have found remission rates significantly higher at 24 weeks in the group of patients treated with venlafaxine extended release than in the combined group of patients treated with conventional antidepressants (59.3% versus 51.5%, respectively). Although it could be argued that the large number of patients included in this trial could overestimate treatment-related clinical differences, the significantly higher rates of remission observed at 24 weeks in this study with venlafaxine extended release compared with conventional treatments, mainly SSRIs, is consistent with results of three recent meta-analysis [Nemeroff et al, 2003;Rudolph, 2002;Thase et al, 2001]. The data obtained from these analyses of double-blinded clinical trials comparing venlafaxine (IR or XR) and selected SSRIs show remission rates significantly higher with venlafaxine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have found remission rates significantly higher at 24 weeks in the group of patients treated with venlafaxine extended release than in the combined group of patients treated with conventional antidepressants (59.3% versus 51.5%, respectively). Although it could be argued that the large number of patients included in this trial could overestimate treatment-related clinical differences, the significantly higher rates of remission observed at 24 weeks in this study with venlafaxine extended release compared with conventional treatments, mainly SSRIs, is consistent with results of three recent meta-analysis [Nemeroff et al, 2003;Rudolph, 2002;Thase et al, 2001]. The data obtained from these analyses of double-blinded clinical trials comparing venlafaxine (IR or XR) and selected SSRIs show remission rates significantly higher with venlafaxine.…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy of venlafaxine immediate (IR) or extended release (XR), as measured by remission rate, has been compared in several earlier meta-analyses with the selective serotonin reuptake inhibitors (SSRIs) fluoxetine, sertraline, paroxetine, citalopram, and fluvoxamine [Nemeroff et al, 2003;Rudolph, 2002;Thase et al, 2001]. These meta-analyses show that venlafaxine may be associated with significantly higher remission rates than those of the studied SSRIs.…”
Section: Introductionmentioning
confidence: 96%
“…Remission, defined as a score of 7 or less on the Hamilton Rating Scale for Depression (HAM-D), was observed regardless of age and gender among 40-55% of patients during venlafaxine and among 31-37% of patients during SSRI ( p < 0.05, between group comparison) . Similar results were obtained in another study showing 45% remission during venlafaxine treatment , and studies have consistently shown a higher remission rate for venlafaxine than for SSRIs with the use of HAM-D (Rudolph, 2002;Nemeroff et al, 2003). Possible explanations for the lower rate observed in our study may be that the patients received fixed dosages and doses were not raised for patients who did not enter remission, and the upper dose limit of 150 mg/day.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the considerable number of clinical trials, evidence of differential efficacy is sparse. The selective serotonin and noradrenalin re-uptake inhibitor (SNRI) venlafaxine has been claimed to be more effective than selective serotonin re-uptake inhibitors (SSRIs) particularly with respect to remission rates (Rudolph 2002;Shelton et al 2005;Smith et al 2002;Thase et al 2001). The proposed mechanism for the differences in efficacy is the dual action of venlafaxine, suggesting an additive benefit of re-uptake inhibition of serotonin and noradrenalin.…”
Section: Introductionmentioning
confidence: 96%